Mycoses and Antifungals: reviewing the basis of a current problem that still is a biotechnological target for marine products - Terra, Luciana; Abreu, Paula A.; Teixeira, Valéria L.; Paixão, Izabel C. P.; Pereira, Rebeca; Leal, Bruno; Lourenço, André Luiz; Rampelotto, Pabulo H.; Castro, Helena C. (Frontiers in Marine Science, 2014)
Currently, the limited number of antifungals available for treating fungal infections, the increased multiresistance, and the adverse effects are the major obstacles for fungal infection therapy. Recently, emergent opportunistic fungus infections have been described and reinforced the requirement of researches aimed at the discovery of novel antifungal agents. Herein we reviewed the main topics about fungi and its related infections, the antifungals available, their mechanism of action and resistance profile. In this work, we pointed fungi as a biotechnological target for finding new options in alternative sources such as marine products with new mechanisms of action to allow treating these dangerous infections.